Synthesis and characterization of hollow silica spheres - Gorsd, Marina Noelia (2015)
The synthesis and characterization of mono-dispersed silica hollow spheres using polystyrene (PS) spheres as template from the hydrolysis and condensation of tetraethylorthosilicate (TEOS) is presented. Successive washing steps with toluene and subsequent calcination at different temperatures were performed, in order to remove the PS template. Furthermore, the PS core removal was studied using different calcination temperatures, but without the prior washing with toluene. The morphology of the materials was studied by scanning electron microscopy and by transmission electron microscopy. A shell formed by silica nanoparticles with 50 nm diameter, being the layer of 100 nm thickness, was observed when using a low concentration of catalyst in the sol-gel reaction. The textural properties of the silica coating, obtained from N2 adsorption-desorption isotherms, depend on the catalyst amount added for the TEOS hydrolysis. From the Fourier transform infrared spectra and the results of the thermogravimetric analyses, it was found that the almost complete removal of the polystyrene core can be directly achieved by calcining at 500 °C, without the need of carrying out any washing and minimizing the formation of cracks in the silica hollow spheres.